Effect of exogenous ABA and fluridone on the germinability of Buglossoides arvensis L seed progeny under contrasting maternal nitrogen levels - Longás, María de Las Mercedes (2018)
Abscisic acid (ABA) is one of main physiological dormancy regulators. During embryogenesis a hormone peak determines dormancy level. Thereafter, ABA concentration and seed embryo sensitivity have a crucial role blocking germination. Unfavorable germination conditions might promote de novo ABA production, thus impeding germination. Maternal effects might generate differences in progeny dormancy. Buglossoides arvensis is a facultative annual weed with differences in physiological dormancy level due to maternal nitrogen fertilizer. The aim of the present work was to evaluate the effect of exogenous ABA and its inhibitor (fluridone, FLU) on the germinability of B. arvensis. A F2 progeny was tested under ABA and FLU gradients at 7, 15 and 20 °C during 30 days. Dose-response curves were fitted and curve parameters compared by ANOVA. Dose-response curves showed that both accessions obtained from unfertilized and nitrogen fertilized plants (sN and cN, respectively) expressed a similar seed germinability. At supra-optimal temperatures FLU stimulated germination. More studies would be necessary to clarify the maternal fertilization effect on germination, its hormonal regulation and its consequences on weed emergence cohorts in the field.